Kajian Etnofisika Konsep Gaya pada Permainan Tradisional Maluku: Bambu Gila - Nuryadin, Muhamad; Rumanama, Labiru; Langi, Arni Arruan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Sekolah Tinggi Islam Blambangan (STIB) Banyuwangi, 2023)
Crazy Bamboo is a traditional game from Maluku Province and North Maluku Province. Some residents also call it a traditional dance. According to the belief of some residents, the bamboo was moving